Investigation of the effects of interdisciplinary science activities on 5th grade students’ creative problem solving and 21st century skills - GÜVEN, İLKNUR (My University, 2022)
In this research, it was aimed to examine the effects of interdisciplinary science activities on 5th grade students' creative problem-solving skills and 21st century skills. The study group consisted of 50 5th grade students, 26 girls and 24 boys, were studying at a public school in Ankara, Çankaya district in the 2018-2019 academic year. The Creative Problem Solving Attribute Inventory and the 21st Century Skills Tests were applied to the students before and after the application. The obtained data were analyzed using a statistical program. The "Dependent Groups tTest" and "Cohen's d" test, which are parametric tests, were used in the analysis of the Creative Problem Solving Attribute Inventory and the 21st Century Skills Test. In line with the evaluations made, it was concluded that interdisciplinary science activities positively affected students' creative problem solving skills and 21st century skills. Suggestions were made based on the findings.
Keywords: Interdisciplinary Teaching; Creative Problem Solving Skills; 21st Century Skills; Interdisciplinary Science Activities